High performance bendable concrete with lower cost and lower embodied carbon - Mohamed Salman Faris (Nanyang Technological University, 2022)
The current cement production in the world leads to enormous amounts of carbon dioxide emissions which cause global warming and many other adverse effects. Research has been ongoing to replace Portland cement (PC) with magnesium silicate hydrate (MSH) cement which helps to tackle this environmental problem. However, the constituents of MSH are very expensive, such as magnesium oxide (MgO) and sodium hexametaphosphate (SHMP). This research will aim to address the high cost of MgO and SHMP and to come up with an alternative MgO and water-reducer that can reduce the overall cost of MSH cement, making it more economical and sustainable. Even though Portland cement is the most commonly used material, concrete is weak in tension. Thus, this led to the emergence of Engineered Cementitious Composites (ECC) to replace the conventional concrete due to its favourable strain-hardening properties. Since ECC is cement based, the research aims to develop a strain-hardening magnesium silicate hydrate (SHMSH) composite with the use of low-cost fibres in order to replace cement based ECC. The main objective is to produce a SHMSH composite that is low in cost, similar to that of ECC. Since the main contributors of the current high cost SHMSH are MgO, SHMP and polymer fibre, this study aims to replace these three materials with cheaper alternative materials without compromising on its strength. A price comparison between the new SHMSH mix design, current expensive SHMSH and cement based ECC will be done. It can be concluded that the new SHMSH design will consist of extremely low cost and high performing MgO from Liao Ning, China due to its satisfactory mechanical properties when formed as both reactive magnesium oxide cement (RMC) and magnesium silicate hydrate (MSH). The high cost SHMP has been replaced with sodium triphosphate (STP), which is a low-cost superplasticizer. Various types of fibres were analysed and both polyethylene(PE) and polyvinyl alcohol (PVA) fibres were suitable for the low cost SHMSH. The SHMSH consisting of these new materials showed remarkable mechanical performance and priced at a cost lower than cement based ECC.